Nutrition Status and Psychosocial Stimulation with the Development of Infants Aged 6-12 Months - Septiyanti, Septiyanti; Seniwati, Seniwati (Sarana Ilmu Indonesia (salnesia), 2025)
One of the factors influencing growth and development is nutritional status. Growth and developmental disorders in infants may result in delays in neuromuscular development, speech ability, emotional regulation, socialization, auditory sensory function, and even autism. This study aimed to examine the relationship between nutritional status and psychosocial stimulation with the growth and development of infants aged 6–12 months in the working area of Tabaringan Health Center, Makassar. A cross-sectional design was employed. The sample consisted of 30 mothers with infants aged 6–12 months who met the inclusion criteria, selected using an accidental sampling technique. The collected data included maternal characteristics, nutritional status, and infant characteristics. Psychosocial stimulation data were obtained through interviews using the HOME questionnaire, consisting of 17 questions. Infant social-personal and language development was assessed using the Denver Developmental Screening Test II (DDST), which included 20 items. Data were analyzed using the Pearson correlation test (Chi-square). The results showed no significant relationship between psychosocial stimulation and both language and personal-social development. However, there was a significant relationship between nutritional status and personal-social development in infants, while no significant relationship was found with language development. Further research is recommended to explore other factors that may influence infant language and personal-social development.